OPTIMIZATION OF PHENOL BIODEGRADATION BY PSEUDOMONAS PUTIDA ISOLATED FROM INDUSTRIAL EFFLUENT - SHWETA; DHANDAYUTHAPANI (International Journal of Pharma and Bio Sciences, 2013)
Bioremediation is a rapidly growing technology to solve the pollution problems all over the world. Providing good environmental condition is one of the important parameter for bacterial bioremediation. In this study, we had optimized bioremediation process to enhance the phenol removal from aqueous solution by a newly isolated and biochemically identified bacteria Pseudomonas putida from an industry effluent. This bacterium was capable of utilizing phenol as a sole source of carbon and was very efficient for phenol degradation at optimized culture condition. 1000 mg.l-1 of phenol was completely degraded at 60th hour of contact time. The optimum pH and temperature for highest phenol degradation was 7 and 350C respectively. Media was supplemented with different concentrations of Iron (Fe) and Selenium (Se) for the growth of Pseudomonas putida and phenol degradation. Maximum phenol degradation of 79.7 % and 80.3% was observed at 0.5mg/l Fe and 0.5mg/l Se respectively. From the results, we conclude that the phenol biodegradation and cultural parameters are interdependent by statistical analysis.